Sustainability partnerships and viticulture management in California. (1st July 2018) - Hillis, Vicken; Lubell, Mark; Hoffman, Matthew
Abstract: Agricultural regions in the United States are experimenting with sustainability partnerships that, among other goals, seek to improve growers' ability to manage their vineyards sustainably. In this paper, we analyze the association between winegrape grower participation in sustainability partnership activities and practice adoption in three winegrowing regions of California. Using data gathered from a survey of 822 winegrape growers, we find a positive association between participation and adoption of sustainable practices, which holds most strongly for practices in which the perceived private benefits outweigh the costs, and for growers with relatively dense social networks. We highlight the mechanisms by which partnerships may catalyze sustainable farm management, and discuss the implications of these findings for improving sustainability partnerships. Taken together, we provide one of the most comprehensive quantitative analyses to date regarding the effectiveness of agricultural sustainability partnerships for improving farm management. Highlights: Sustainability partnerships promote collaborative governance in agriculture. Growers who participate in partnerships manage winegrapes more sustainably. Growers with strong social networks manage winegrapes more sustainably. Partnerships have the most impact when practices involve perceived benefits. Practices that involve perceived cooperative dilemmas pose a greater challenge.